The living prism : itineraries in comparative literature - Kushner, Eva (Published for Carleton University by McGill-Queen's University Press, 2001)
"To play in important role in the human sciences, comparative literature first had to free itself of a number of restrictive habits, such as an insufficiently critical literary history. To do this, scholars had to think theoretically but without yielding to the temptation of letting theory become an end in itself. Eva Kushner demonstrates that, despite strong pressure to be a more rigorous science, recent directions in comparative literature have realized that the validity of knowledge must constantly be tested, becoming increasingly more open to individuality, difference, and life situations rather than proposing universalizing statements about literary values."--Jacket.